A Survey of Issues and Approaches in Mobile Cloud Computing - B. Muthu Kumar, (AG Volumes, 2022)
(MCC) Mobile cloud computing refers to the provision of the cloud computing services inside a mobile context. MCC utilises both mobile networks as well as cloud computing to provide mobile users with the best possible experience. Mobile devices don't need to have strong configurations such as CPU speed, storage capabilities, and so on, since all data as well as difficult computing modules may be processed in the clouds under mobile cloud computing. An overview of MCC applications' needs and current solutions is presented in this study. We also cover architecture, applications, main features, security challenges, advantages and disadvantages, and maybe a solution for mobile cloud computing.